Risk of diabetic ketoacidosis of SGLT2 inhibitors in patients with type 2 diabetes: a systematic review and network meta-analysis of randomized controlled trials - Yang, Shiwen; Liu, Ying; Zhang, Shengzhao; Wu, Fengbo; Liu, Dan; Wu, Qingfang; Zheng, Hanrui; Fan, Ping; Su, Na (Frontiers in Pharmacology, 2023)
Background: Sodium-glucose-cotransporter-2 (SGLT2) inhibitors have proven to be effective in improving glycemic control in patients with type 2 diabetes mellitus (T2DM). But the risk of diabetic ketoacidosis (DKA) in patients remain unclear. The purpose of this study is to conduct this systematic review and network meta-analysis for the risk of DKA of SGLT2 inhibitors in patients with T2DM. Methods: We searched for randomized controlled trials (RCTs) concerning SGLT2 inhibitors in patients with T2DM in PubMed, Embase (Ovid SP), Cochrane Central Register of Controlled Trials (Ovid SP), and ClinicalTrials.gov from inception to January 2022. The primary outcomes were the risk of DKA. We assessed sparse network with fixed-effect model and consistency model in frequentists framework with a graph-theoretical method by netmeta package in R. We assessed the evidence quality of evidence of outcomes according to the grading of recommendations assessment, development, and evaluation (GRADE). Results: Thirty-six studies involving 52,264 patients were included. The network showed that there was no significant difference observed among SGLT2 inhibitors, other active antidiabetic drugs, and placebo in the risk of DKA. There was no significant difference in DKA risk between different doses of SGLT2 inhibitors. The certainty of the evidence ranged from very low to moderate. The probabilities of rankings and P-score showed that compared to placebo, SGLT2 inhibitors might increase the risk of DKA (P-score = 0.5298). Canagliflozin might have the higher DKA risk than other SGLT2 inhibitors (P-score = 0.7388). Conclusion: Neither SGLT2 inhibitors nor other active antidiabetic drugs were associated with an increased risk of DKA compared to placebo, and the risk of DKA with SGLT2 inhibitors was not found to be dose-dependent. In addition, the use of canagliflozin was less advisable compared with other SGLT2 inhibitors according to the rankings and P-score.